Politicized policy access: The effect of politicization on interest group access to advisory councils. (17th February 2020) - Willems, Evelien
Abstract: Current scholarship often concludes that technical expertise is one of the most important commodities for interest groups wishing to gain access to political‐administrative venues. Less attention has been given to politicization and the scope of societal support that interest groups bring to bear. Specifically, I hypothesize that the capacity of interest groups to supply broad societal support is decisive for gaining access in highly politicized policy domains. To test this expectation, the article combines a mapping of interest group membership in 616 Belgian advisory councils with survey data from more than 400 organized interests. The empirical analyses demonstrate that interest groups with broad support are more likely to gain access to advisory councils in highly politicized policy domains, but this effect is negatively moderated when interest groups involve their constituencies intensely in advocacy processes.